2013
DOI: 10.1142/s0218271813500065
|View full text |Cite
|
Sign up to set email alerts
|

ON ANALYTICAL SOLUTIONS OF f(R) MODIFIED GRAVITY THEORIES IN FLRW COSMOLOGIES

Abstract: A novel analytical method for f (R) modified theories without matter in Friedmann-Lemaitre-Robertson-Walker spacetimes is introduced. The equation of motion for the scale factor in terms of cosmic time is reduced to the equation for the evolution of the Ricci scalar R with the Hubble parameter H. The solution of equation of motion for actions of the form of power law in Ricci scalar R, is presented with a detailed elaboration of the action quadratic in R. The reverse use of the introduced method is exemplified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The behavior of the system near the non-gaussian fixed point for any g * and λ * is then described by a f (R) modified gravity theory with f (R) = R 2 . The importance of R 2 effective action, which can be analytically solved [25,26,27], was recently stressed in [14,15], based on Ansatz k 2 ∼ R. In this paper the relation k 2 ∼ R is derived from the scale-setting procedure, together with the coefficient of proportionality.…”
Section: Non-gaussian Fixed Point In Einstein-hilbert Truncationmentioning
confidence: 99%
“…The behavior of the system near the non-gaussian fixed point for any g * and λ * is then described by a f (R) modified gravity theory with f (R) = R 2 . The importance of R 2 effective action, which can be analytically solved [25,26,27], was recently stressed in [14,15], based on Ansatz k 2 ∼ R. In this paper the relation k 2 ∼ R is derived from the scale-setting procedure, together with the coefficient of proportionality.…”
Section: Non-gaussian Fixed Point In Einstein-hilbert Truncationmentioning
confidence: 99%
“…Recently the same analysis has been performed and for a general perfect fluid with nonzero equation of state parameter [57], whereas for some locally rotational spacetimes the Noether point symmetry classification of f (R)-cosmology can be found in [60]. Some other f (R)-models with closed-form solutions can be found in [61], while the application of point transformations in f (R)-gravity in static spherically symmetric spacetimes can be found in [62,63] Another geometric selection rule which is based upon the group invariant transformations of the Wheeler-DeWitt equations was introduced in [64]. It has been shown that the existence of a Lie point symmetry for the WheelerDeWitt equation is equivalent with the existence of a Noetherian conservation law for the classical field equations.…”
Section: Introductionmentioning
confidence: 90%
“…where h is the value for the integral of motion described by the Hamiltonian for Lagrangian (40). In a similar way as before we construct the autonomous first integral [62]…”
Section: Ermakov-pinney Systemmentioning
confidence: 99%